Integralna wizja osoby w ujęciu Edmunda Bojanowskiego - Konopko, Dariusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article is an attempt to present an integral view of Bl. Edmund Bojanowski per person. He was not a philosophical educator, but he was in his thoughts to the representatives of this direction. He based his views on theological and philosophical grounds and could in a sense be attributed to the personalists. In his life he bent primarily on the child and his upbringing. An important place in his notes and thoughts is occupied by the family as well as the role of man and woman in education. The dignity that is the indispensable feature of humanity is in blessedness. Edmund’s starting point for his reflections on the person.